Pre-Treatment with Ketorolac Alongside Venous Occlusion Can Reduce the Pain of Propofol Injection; A Quasi-Experimental Study - Haider, Syed Zulfiqar; Khoso, Mujahid Ali; Ayaz, Saeed Bin; Abbas, Muhammed Ali; Rehman, Habib Ur; Iftikhar, Hina (Pakistan Armed Forces Medical Journal, 2022)
Objective: To investigate the efficacy of Ketorolac with and without venous occlusion to relieve pain associated with Propofol injection. Study Design: Quasi-experimental study. Place and Duration of Study: Anesthesiology Department, Combined Military Hospital Multan, from Jan 2020 to Mar 2021. Methodology: One hundred and twenty patients of age more than 16 years with ASA physical status 1 and 2, undergoing elective surgery at Combined Military Hospital Multan were selected. Patients were allocated into the groups to receive Saline with sham occlusion (group-A), 10 mg Ketorolac with sham occlusion (Group-B), or 10 mg Ketorolac with full venous occlusion for 120 seconds (Group-C). Before surgery, the patients were asked to rate any local discomfort on a scale of 0-3 ten seconds after receiving a Propofol injection. On the seventh post-operative day, all the patients were handed a questionnaire to describe any untoward symptoms. Results: The mean age of the patients was 48.3 ± 2.8 years (range: 16 to 80 years). Mild discomfort was experienced by 4 (10%) patients, while 12 (30%) patients had moderate pain and 5 (12.5%) patients experienced severe pain in Group-A. In group- B, 16 (40%) patients had mild discomfort, 7 (17.5%) had moderate pain, and 5 (12.5%) had severe pain. In Group-C, 10 (25%) individuals experienced mild discomfort, 5 (12.5%) patients experienced moderate pain, whereas none of the patients experienced severe pain (p<0.001). Patients among the three groups reported no significant difference in post-injection venous sequelae. Conclusion: Pre-treatment with 10 mg Ketorolac and venous occlusion for 120 seconds...